Longitudinal Descriptive Study of Science Process Skill Growth in Basic Physics Practicum - Dahlan, Ahmad; Agustini, Sri; Yani, Ahmad; Manarfah, Laode (ARRUS Journal of Social Sciences and Humanities, 2025)
Science Process Skills (KPS) is a basic competency in science education that plays an important role in developing students' scientific thinking skills and science literacy. This study aims to describe the growth of science process skills of Physics Education students based on the KPS indicators reflected in the Basic Physics practicum report. The study used a longitudinal type quantitative descriptive approach with 54 students of the Physics Education Study Program, FMIPA, State University of Makassar. Data were obtained from the assessment of student practicum reports during four meetings using the PPP rubric which consisted of six indicators: formulating problems, formulating hypotheses, compiling operational definitions of variables, collecting data, analyzing data, and drawing conclusions. Data analysis was carried out by calculating the mean value, standard deviation, and score change between meetings (Δ). The results showed an increase in the average PPP score from 2.58 at the first meeting to 3.42 at the fourth meeting, with a growth of ΔP=+0.84. The indicator with the highest improvement was analyzing the data and drawing conclusions (Δ=+0.90), while the lowest improvement occurred in the indicator formulating the problem (Δ=+0.75). These findings show that Basic Physics practicum activities play an effective role in fostering students' scientific thinking skills gradually. This study recommends that practicum activities in higher education emphasize explicit guidance on advanced PPP indicators, as well as strengthen reflective activities and scientific communication in practicum reports.